Atmospheric CF2Cl2 and CFCl3 in Antarctica (abstract) - Hirota, Michio; Makino, Yukio; Chubachi, Shigeru; Shiobara, Masataka; Muramatsu, Hisafumi; Murayama, Haruta (1986)
P(論文) departmental bulletin paper